Socio-Personal Characteristics of Fishermen Operating Marine Plywood Crafts in Kerala - S., Balasubramaniam; M.K., Kandoran; Mohan, Braj (Fishery Technology, 2025)
This paper analyses the socio-personal characteristics of fishermen who operate the marine plywood crafts in Kerala, India. The comparative profiles of the fishermen operating marine plywood crafts, dugout canoes and plank-built crafts are presented. The results revealed that the fishermen operating marine plywood crafts had higher mean scores on annual income, number of fishing days in a year, number of fishing gears used and total investment than the other two categories.